PENGGUNAAN MODEL PEMBELAJARAN LEARNING CYCLE BERBASIS LINGKUNGAN TERHADAP PEMAHAMAN SISWA PADA MATERI EKOSISTEM DI KELAS VII SMP NEGERI 1 KRAMATMULYA - Neng Wulan Evi Juliani; Abdul Muis; Agus Prianto (Quagga : Jurnal Pendidikan dan Biologi, 2015)
Usage-Based Learning Cycle models Learning Environment Students Against Understanding to Content Ecosystem (An Experiment In Class VII SMP Negeri 1 Kramatmulya) Biology Education Program Teacher Training and Education Faculty of the University of Brass. This research is motivated by the low quality of education today, especially in the junior high school level. This is caused by the lack of facilities and infrastructure that support the achievement of the expected learning objectives, in line with it. This study aims to determine the effectiveness of the use of the Learning Cycle models of students' understanding of the concept of the ecosystem. The method used is the method of True Experimental Design that aims to find the relationship Learning Cycle models to the understanding of class VII students of SMP Negeri 1 Kramatmulya. In this method, taken as many classes with 2 Random selected for experiment class and control class. 2 class (70 students) who used the class VII. A and VII. F from a population of 230 seventh grade students of SMP Negeri 1 Kramatmulya in 2013. Learning outcomes data retrieval using achievement test instrument (30 items) and anggket student responses to the application of the learning model. Analysis of the data using statistical hypothesis test - t and t value of 4.27 is obtained at significant level () of 0.05 and 2.66 obtained ttable then t t table, so it can be concluded that the t value is outside the interval t table , which means that there is a difference between the experimental class that uses the Learning Cycle models and control classes that do not use the Learning Cycle models. Or in other words Learning Cycle Model for Understanding effective use of class VII students of SMP Negeri 1 Kramatmulya on ecosystems material with an average value (mean) value of the test in the experimental class was 75.81. While the average test scores in the control class is 64.27. it can be said that the students' understanding of classes taught by the Learning Cycle models better than the class being taught by not using the Learning Cycle Model.Kata Kunci :    Ekosistem, Model Learning Cycle, True Experimental Design